Remoção de metais provenientes de drenagem ácida de minas em reator anaeróbio horizontal com biomassa imobilizada - Melo Júnior, Omar Mendes De (2016)
The mining activity, beyond positively influence the economic and social development of the country presents a major environmental liabilities: wastewater rich in sulfate. Better known as Acid Mine Drainage, AMD, these wastewaters are from most of the time, mining of coal and heavy metals where the mineral sulfides are oxidized naturally sulphate and the main features low pH and high concentrations metals. There are several treatments for AMD, being physical, chemical and biological. Physicochemical methods consist of neutralization and precipitation of heavy metals, with high operating costs. Already biological methods are an excellent alternative for the treatment and remediation of AMD, because through anaerobic reactors, promote the reduction of sulfate and the recovery of metals. In this study, a horizontal anaerobic fixed bed reactor was used, HABR, for the bioremediation of synthetic AMD, having its interior filled with polyurethane foam for immobilization of biomass and ethanol as carbon source, relationship between the chemical oxygen demand, and sulfate, COD/SO42- and hydraulic retention time, TDH, 24 and 36 hours. Throughout this experiment was varied conditions with respect to concentration of COD and SO42-, HRT and filler metals. The pH, SO42-, sulfide, COD and metals, were very satisfactory in relation to the reactor performance for all operating phases. Increasing the HRT of 24 to 36 hours, it was observed that the removal efficiency values were significant compared with the previous stages. Thus, the study demonstrated its effectiveness for treating AMD in a synthetic HABR, achieving high removal values.